Pneumococcal Polysaccharide Vaccination Elicits IgG Anti-A/B Blood Group Antibodies in Healthy Individuals and Patients with Type I Diabetes Mellitus - Wolfram, Wendelin; Sauerwein, Kai M. T.; Binder, Christoph J.; Eibl-Musil, Nicole; Wolf, Hermann M.; Fischer, Michael B. (Frontiers in Immunology, 2016)
Hypothesis Blood group antibodies are natural antibodies that develop early in life in response to cross-reactive environmental antigens in the absence of antigen encounter. Even later in life structural similarities in saccharide composition between environmental antigens such as bacterial polysaccharides and blood group A/B antigens could lead to changes in serum levels, IgM/IgG isotype, and affinity maturation of blood group anti-A/B antibodies. We addressed the question whether immunization with pneumococcal polysaccharide (PnP) vaccine Pneumo 23 Vaccine “Pasteur Merieux” (Pn23) could have such an effect in patients with type I diabetes mellitus (DM I), an autoimmune disease where an aberrant immune response to microbial antigens likely plays a role. Methods Anti-PnP IgM and IgG responses were determined by ELISA, and the DiaMed-ID Micro Typing System was used to screen anti-A/B antibody titer before and after Pn23 immunization in 28 healthy individuals and 16 patients with DM I. In addition, surface plasmon resonance (SPR) technology using the Biacore® device and a synthetic blood group A/B trisaccharide as the antigen was applied to investigate IgM and IgG anti-A/B antibodies and to measure antibody binding dynamics. Results All healthy individuals and DM I patients responded with anti-PnP IgM and IgG antibody production 4–6 weeks after Pn23 immunization, while no increase in blood group anti-A/B antibody titer was observed when measured by the DiaMed-ID Micro Typing System. Interestingly, isotype-specific testing by SPR technology revealed an increase in blood group anti-A/B IgG, but not IgM, following Pn23 immunization in both patients and controls. No change in binding characteristics of blood group anti-A/B antibodies could be detected following Pn23 vaccination, supporting the assumption of an increase in IgG antibody titer with no or very little affinity maturation. Conclusion The study provides evidence for epitope sharing between pneumococcal polysaccharides and blood group ABO antigens, which leads to a booster of blood group anti-A/B antibodies of the IgG isotype after Pn23 immunization in healthy individuals. Manifest autoimmunity such as present in DM I patients has no additional effect on the cross-reactive antibody response against pneumococcal polysaccharides and blood group antigens.